The Truth About Predispositions: Exposing The Gap Between What We Say and How We Feel - Galluch, Pamela S.; Serrano, Marta Miller- (Journal of Strategic Innovation and Sustainability, 2018)
This study examines how predispositions can cause individuals to over or underreact to situations, thus affecting their report of stress and performance. To do this, we examined three personality characteristics: social desirability, fear of negative evaluation, and locus of control, to see how they correlate with perceived stress, objective strain, and performance. We found that the fear of negative evaluation is a root cause of strain, while social desirability causes one to report stress, but not feel it. We also found that having an internal locus of control positively affects performance and that perceived stress causes performance to decrease.